Supplementation of diets for Santa Ines sheep with organic and inorganic zinc sources - Vilela, Flávio Garcia; Zanetti, Marcus Antonio; Netto, Arlindo Saran; De Freitas Júnior, José Esler [UNESP]; Rennó, Francisco Palma; Venturelli, Beatriz Conte; de Souza Canaes, Taissa (FapUNIFESP (SciELO), 2012)
This research was conducted with objective to evaluate the effect of different zinc (Zn) sources and doses in the diet for Santa Ines sheep. Forty lambs at weaning, with 18.4 kg of body weight were supplemented with three different sources of zinc (zinc oxide (ZnO), zinc amino acid and zinc proteinate) and three doses of zinc (200, 400 and 600 mg/kg DM) added to the basal diet. At every 28 days, animals were weighted and blood samples were collected for analyses of zinc (Zn), alkaline phosphatase and immunoglobulin G (IgG) and M (IgM). At the end of experiment, liver samples were collected for determination of the hepatic zinc levels. Zinc was analyzed with atomic absorption spectrophotometer, while phosphatase alkaline and immunoglobulins G and M were analyzed using Laborlab and Bioclin kits, respectively. There was no effect of diets on phosphatase alkaline levels and hepatic zinc, but there was difference in the plasmatic zinc levels and IgG and IgM levels. Based on the accumulation of hepatic zinc, the estimate of the zinc bioavailability, through the regression equation, showed that supplementation with organic and inorganic sources of zinc did not differ in the diet of Santa Ines sheep. © 2012 Sociedade Brasileira de Zootecnia.
Keywords: Bioavailability; Immunoglobulin; Lambs; Minerals